Becoming a Social Detective: Observational and Probing Strategies for Eliciting Honest Interview Data - Helmi Handoko; Eprianto; Fajri Ismail; Muhammad Win Afgan (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study is motivated by the persistent challenge of social desirability bias and the presence of “social masks” in interview interactions, which often obstruct the acquisition of authentic and truthful data. Conventional question-and-answer techniques frequently fail to penetrate respondents’ defensive filters. This research aims to develop a systematic framework for adaptive observational techniques through a “social detective” approach to enhance the validity of qualitative data. This study employs a qualitative ethnographic design, where the researcher serves as the primary instrument. Data were collected through semi-structured interviews, investigative probing, and participant observation, and analyzed inductively using the Miles and Huberman interactive model. The findings reveal that data honesty can be enhanced through three key techniques: (1) establishing strategic rapport to reduce respondents’ defensiveness, (2) employing strategic silence to stimulate self-disclosure through the psychological mechanism of horror vacui, and (3) conducting nonverbal cross-checks to identify behavioral leakage and inconsistencies between verbal statements and body language. The study concludes that this investigative approach effectively mitigates information bias by accessing respondents’ “backstage” realities while maintaining strict adherence to research ethics.